Changes in the immunogold electron-microscopic localization of calpain in bovine skeletal muscle induced by conditioning and high-pressure treatment - Borjigin, G.(Niigata Univ. (Japan). Faculty of Agriculture); Yamamoto, S; Sugiyama, T; Nishiumi, T; Suzuki, A (Bioscience, biotechnology, and biochemistry, 2006)
Changes in the localization of calpain in conditioned and pressurized bovine skeletal muscles were investigated by immunogold electron-microscopy. In the muscle immediately after thawing (control), the relative distributions of colloidal particles statistically calculated by counting the colloidal particles were about 65% and 35% in the I-band/Z-disk and A-band regions, respectively. In the muscle conditioned for 7 days, distribution of colloidal particles was more than two times greater in both the I-band/Z-disk and A-band regions than in the control muscle. Almost no change in either the absolute concentration or relative distribution of the colloidal particles was detectable during further storage. In the muscle exposed to a pressure of 100 MPa or 200 MPa, slightly more immunogold was detected in the sarcomere than in that of the control muscle. Increasing pressure up to 300 MPa enabled high-density particles to be seen throughout the sarcomere. Conversely, few particles were detected in the sarcomere of the muscle exposed to 400 MPa. These electron-microscopic observations were confirmed from the statistical analysis as with the conditioned muscles. It was clear from the results obtained that the pressure-induced changes in calpain localization were much more pronounced than those from conditioning.